DEVELOPMENT OF PROFESSIONAL COMPETENCES OF FUTURE EDUCATORS BASED ON THE ACMELOGICAL APPROACH - Khudoymurodova Dilafruz (Zeta Repository, 2023)
The change of the social and cultural situation in Uzbekistan accelerated the priority of ideas and goals based on humanitarianism in the science of pedagogy. The change of educational paradigm created complex pedagogical processes. This requires the modernization of the continuous education system, especially the content of higher pedagogical education, based on the acmeological approach.